Acne fuminans in the course of oral isotretinoin treatment. Presentation of cases - Magdalena Kręgiel; Anna Żuchowska; Katarzyna Tomaszewska; Agnieszka Wojciechowska; Anna Jędrowiak; Katarzyna Tabara; Wojciech Bienias; Joanna Krzysiek; Andrzej Kaszuba; Ewa Trznadel-Grodzka (Our Dermatology Online, 2016)
Isotretinoin is considered a gold standard in treating severe cases of acne. It brings lots of benefits but on the other hand can cause series of undesirable side-effects. I present 2 cases of patients suffering from acne fulminans in the course of treatment with oral isotretinoin. Acne fulminans is a very severe systemic disease and its course is difficult to foresee. The most important is rapid diagnosis and implementation of treatment. Systemic corticosteroids combined with isotretinoin or high does of antibiotics are the most effective. The alternative methods are: dapsone, infliximab.